Is anemia in children with sleep disordered breathing actually a consequence of chronic disease? - Akcan, Fatih Alper; Dündar, Yusuf; Bayram Akcan, Hümeyra; Uluat, Ahmet; Cebeci, Derya; Sungur, Mehmet Ali (The European Research Journal, 2018)
Objective. We aimed to investigate iron metabolism and laboratory findings of anemia in children undergoing adenotonsillectomy for sleep disordered breathing.Methods. Consecutive children undergoing adenoidectomy/adenotonsillectomy for sleep disordered breathing between January 2013 and January 2015 were investigated. Routine preoperative blood tests including blood count and iron studies were analyzed. Subgroup analyses were performed addressing to the severity of sleep disordered breathing, age and duration of symptoms. Results were compared between subgroups and normal values.Results. The study included 171 children. The mean age was 5.44 ± 2.62 years. The mean hemoglobin level was 11.87 ± 1.125 gr/dL and 24 (14%) out of 171 patients had anemia (< 11 gr/dL). The mean ferritin levels were 23.23 ± 17.27 µg/L and 21.27 ± 15.44 µg/L in patients with anemia and non-anemic patients, respectively (p = 0.572). Ferritin levels decreased in only 8 (33%) out of 24 patients with anemia. The mean age, body mass index, hematocrit, mean corpuscular volume, unsaturated iron binding capacity and serum iron levels decreased in patients with anemia. The rate of anemia significantly increased in children less than or equal to 3 years of age (p = 0.020). There was no significant association between hemoglobin levels and sleep disordered breathing clinical score or duration of symptoms.Conclusion. The association between low iron status and sleep disordered breathing has previously published. Unfortunately, the type of anemia is still unclear. Our results supposed that the anemia of chronic disease secondary to chronic inflammatory process might play a role in pathogenesis of anemia in patients with sleep disordered breathing.